Flame-retardant lyocell fiber and preparation method thereof
By using a fiber core composed of a first flame retardant and cellulose in lyocell fiber, and forming a modified graphene oxide layer loaded with a second flame retardant on its surface, the flame retardant durability of existing flame retardant fibers is solved. and fiber performance issues to achieve efficient flame retardant performance and excellent fiber strength.
Patent Information
- Application Number
- CN202411601264.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing flame-retardant lyocell fibers have problems such as poor flame retardant durability, easy flame retardant layer to fall off, high preparation energy consumption, insufficient fiber specific strength, and poor stability of the spinning process.
A flame-retardant lyocell fiber is used that includes a fiber core and a skin layer directly formed on the surface of the fiber core. The fiber core is composed of a first flame retardant and cellulose, and the skin layer is composed of modified graphene oxide loaded with a second flame retardant. , formed through double diffusion effect and micro-swelling effect.
The effect of good flame retardant performance, LOI ≥ 28 % of the oxygen limit index, good flame retardant cortex uniformity, difficulty falling off, excellent fiber performance, and high strength than strength.
Smart Images

Figure CN119352189A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardant fibers, and in particular to a flame retardant lyocell fiber and a preparation method thereof. Background Art
[0002] As a new generation of regenerated cellulose fiber, Lyocell fiber has structural characteristics such as high degree of polymerization, crystallinity and orientation, and thus has excellent mechanical properties, water absorption and swelling properties, and outstanding fibrillation properties. However, Lyocell fiber is flammable, and flame retardant modification of Lyocell fiber to obtain flame retardant Lyocell fiber with good flame retardant properties has always been a key research topic in the field of fiber modification. Flame retardant Lyocell fiber has the characteristics of resistance to melt dripping and not easy to produce thick smoke, and its strength drop after flame retardant treatment is not as obvious as flame retardant viscose, so it has attracted much attention.
[0003] At present, there are two main ways to modify lyocell fibers to make them flame retardant:
[0004] (1) The flame retardant treatment of lyocell fabric is carried out by preparing the flame retardant and then finishing the fabric, and the flame retardant is attached to the fiber surface. This treatment has the problems of uncontrollable uniformity of flame retardant coverage, poor flame retardant durability, easy detachment of the flame retardant layer, and high energy consumption during the preparation process.
[0005] (2) The flame retardant is prepared into a solution of NMMO and blended with the NMMO before lyocell spinning. This treatment method (blending) has very high requirements for the preparation and selection of flame retardants. It must take into account acid and alkali resistance, heat resistance, dispersibility and compatibility with the NMMO system. It also has a certain impact on the stability of the spinning process of lyocell fibers. In particular, this treatment method requires adding a large amount of flame retardant to the fiber to obtain a better flame retardant effect. Generally speaking, the addition amount is 15 to 50 wt.%. Under normal circumstances, the higher the flame retardant content, the better the flame retardant effect, but the fiber performance will decrease, especially the fiber specific strength will decrease significantly.
[0006] In summary, it is necessary to provide a flame retardant lyocell fiber and a preparation method thereof to solve the contradiction between flame retardancy and spinnability (mainly referring to fiber specific strength). Summary of the invention
[0007] In view of the above analysis, an embodiment of the present invention aims to provide a flame-retardant lyocell fiber and a preparation method thereof, so as to solve at least one of the problems of existing flame-retardant lyocell fibers, such as poor flame retardant durability, easy detachment of the flame retardant layer, high preparation energy consumption, insufficient fiber specific strength, and poor stability of the spinning process.
[0008] The present invention provides a flame retardant lyocell fiber, comprising a fiber core and a skin layer directly formed on the surface of the fiber core, wherein the fiber core comprises a first flame retardant and cellulose, and the skin layer comprises modified graphene oxide loaded with a second flame retardant.
[0009] Specifically, the fiber core is formed by spinning a spinning solution including a first flame retardant and cellulose.
[0010] Furthermore, the skin layer is directly formed on the surface of the fiber core when the fiber core enters a coagulation bath including modified graphene oxide loaded with a second flame retardant.
[0011] Furthermore, the skin layer is directly formed on the surface of the fiber core through double diffusion effect and micro-swelling effect.
[0012] Specifically, the first flame retardant is one or more of kaolin, montmorillonite, silica powder, and talc powder.
[0013] Specifically, in the fiber core, the mass content of the first flame retardant is 8-11%, and / or the diameter of the fiber core is 7-12 μm.
[0014] Specifically, the second flame retardant is a mixture of component A and component B, and the mass ratio of component A to component B is 1:1-9;
[0015] Wherein, component A is one of melamine, dicyandiamide, guanidine carbonate, guanidine phosphate, condensed guanidine phosphate, guanidine sulfamate and their derivatives; component B is tetrakis(hydroxymethyl)phosphonium sulfate or KWB.
[0016] Specifically, in the modified graphene oxide loaded with the second flame retardant, the mass ratio of the second flame retardant to the graphene oxide is 10 to 20:1.
[0017] Specifically, in the skin layer, the mass content of the modified graphene oxide is 0.5-2%; and / or the thickness of the skin layer is 0.5-2 μm.
[0018] The present invention also provides a method for preparing the flame-retardant lyocell fiber, comprising the following specific steps:
[0019] S1: taking a dispersant, a first flame retardant, and deionized water to prepare a first flame retardant dispersion;
[0020] S2: mixing the first flame retardant dispersion with the cellulose pulp and the first NMMO aqueous solution, heating, dissolving and dehydrating to obtain a spinning solution;
[0021] S3: preparing a modified graphene oxide dispersion loaded with a second flame retardant, and mixing the modified graphene oxide dispersion with a second NMMO aqueous solution to prepare a coagulation bath solution;
[0022] S4: After spinning, the spinning solution enters a coagulation bath and is post-treated to obtain the flame-retardant lyocell fiber.
[0023] Specifically, the composition of the first flame retardant dispersion in step S1 is 0.5-2 parts by mass of dispersant, 5-15 parts by mass of first flame retardant, and 80-100 parts by mass of water; wherein the dispersant is a modified lignin sulfonate dispersant.
[0024] Specifically, in step S2, the mass ratio of the first flame retardant dispersion, cellulose pulp, and first NMMO aqueous solution is 10-20:55-65:20-25; wherein the mass concentration of NMMO in the first NMMO aqueous solution is 50%, and the mass concentration of NMMO in the spinning solution is 72-88%.
[0025] Specifically, the volume ratio of the modified graphene oxide dispersion to the second NMMO aqueous solution in step S3 is 1:1; wherein the mass concentration of the modified graphene oxide dispersion is 5% to 15%, and the solvent is water; and the mass concentration of NMMO in the second NMMO aqueous solution is 10% to 20%.
[0026] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0027] 1. The flame-retardant lyocell fiber provided by the present invention has good flame retardant properties, a limiting oxygen index LOI ≥ 28%, and a flame-retardant cortex with good uniformity, which is not easy to fall off (or almost impossible to fall off), and has excellent fiber properties and high specific strength.
[0028] The present invention provides a flame retardant lyocell fiber, comprising a fiber core and a skin layer directly formed on the surface of the fiber core, wherein the fiber core comprises a first flame retardant and cellulose, and the skin layer comprises modified graphene oxide loaded with a second flame retardant.
[0029] The cortex is obtained by introducing modified graphene oxide into the fiber surface of the fiber core, and the fiber core and the cortex are a whole. Specifically, the modified graphene oxide enters the surface of the fiber core from the coagulation bath solution due to the double diffusion effect; at the same time, the modified graphene oxide enters the surface fiber, and a slight volume expansion occurs due to the micro-swelling effect, thereby forming a structure different from the inside of the fiber core, that is, the cortex described in the present invention.
[0030] It is worth emphasizing that the above-mentioned "fiber core + skin" structure is significantly different from the existing skin-core composite fibers.
[0031] In the present invention, in order to achieve the flame retardant effect of the cortex, modified graphene oxide (GO) loaded with a second flame retardant is used as its main component. Due to the high specific surface area and rich active groups of graphene oxide, the second flame retardant can be firmly adsorbed on the surface of GO without affecting its flame retardant properties; and because graphene oxide provides better sealing and thermal conductivity, the cortex can better absorb heat, promote carbonization and self-extinguishing, and the flame retardant properties are further improved.
[0032] During the preparation of the flame-retardant fiber, a solution containing graphene oxide is used for treatment in the coagulation bath stage, under the premise that the inner core fiber has not yet been completely solidified. The modified graphene oxide in the solution enters the surface fiber of the core due to the double diffusion effect and the micro-swelling effect to form a flame-retardant cortex. Therefore, the cortex and the core are actually a whole, and the modified graphene oxide in the cortex and the surface fiber are inseparable, which fundamentally avoids the defects of uneven distribution and easy shedding of the flame-retardant cortex added by post-treatment in the prior art. Unless the flame-retardant fiber is subjected to an external force sufficient to destroy the basic structure of the fiber, the cortex will basically not fall off.
[0033] It is worth noting that the flame retardant effect of the cortex is actually the result of the joint effect of the first flame retardant and the second flame retardant, because the surface layer of the fiber core is actually composed of the first flame retardant and cellulose, that is, the cortex includes the first flame retardant, cellulose and modified graphene oxide loaded with the second flame retardant.
[0034] Since the amount of flame retardant added to the core (i.e., the fiber body) of the present invention is very small, not exceeding 11wt.%, under the condition of equal flame retardancy, the breaking strength of the flame retardant fiber is better than that of the flame retardant fiber in the prior art, which can reach 4.5cN / dtex.
[0035] 2. The flame-retardant fiber disclosed in the present invention has relatively common and easily available raw materials, and the preparation process can be realized by existing equipment, with low operating difficulty, mild process conditions and short production cycle; and it has good stability during the spinning process, and can realize factory-based continuous production, which is suitable for wide promotion and large-scale application, and has great market prospects and application potential.
[0036] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0038] Figure 1 Schematic diagram of the structure of flame-retardant lyocell fiber.
[0039] Reference numerals:
[0040] 1. First flame retardant; 2. Second flame retardant; 3. Fiber core; 4. Cortex. DETAILED DESCRIPTION
[0041] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0042] The present invention provides a flame retardant lyocell fiber, comprising a fiber core and a skin layer directly formed on the surface of the fiber core, wherein the fiber core comprises a first flame retardant and cellulose, and the skin layer comprises modified graphene oxide loaded with a second flame retardant.
[0043] Specifically, the fiber core is formed by spinning a spinning solution including a first flame retardant and cellulose.
[0044] Furthermore, the skin layer is directly formed on the surface of the fiber core when the fiber core enters a coagulation bath including modified graphene oxide loaded with a second flame retardant.
[0045] Furthermore, the skin layer is directly formed on the surface of the fiber core through double diffusion effect and micro-swelling effect.
[0046] Specifically, the modified graphene oxide enters the surface layer of the fiber core from the coagulation bath solution due to the double diffusion effect; at the same time, the modified graphene oxide enters the surface fiber and undergoes a slight volume expansion due to the micro-swelling effect, thereby forming a structure different from the interior of the fiber core, which is the cortex described in the present invention.
[0047] It is worth emphasizing that the above-mentioned "fiber core + skin" structure is significantly different from the existing skin-core composite fibers.
[0048] In the present invention, in order to achieve the flame retardant effect of the cortex, modified graphene oxide (GO) loaded with a second flame retardant is used as its main component. Due to the high specific surface area and rich active groups of graphene oxide, the second flame retardant can be firmly adsorbed on the surface of GO without affecting its flame retardant properties; and because graphene oxide provides better sealing and thermal conductivity, the cortex can better absorb heat, promote carbonization and self-extinguishing, and the flame retardant properties are further improved.
[0049] During the preparation of the flame-retardant fiber, a solution containing graphene oxide is used for treatment in the coagulation bath stage, under the premise that the inner core fiber has not yet been completely solidified. The modified graphene oxide in the solution enters the surface fiber of the core due to the double diffusion effect and the micro-swelling effect to form a flame-retardant cortex. Therefore, the cortex and the core are actually a whole, and the modified graphene oxide in the cortex and the surface fiber are inseparable, which fundamentally avoids the defects of uneven distribution and easy shedding of the flame-retardant cortex added by post-treatment in the prior art. Unless the flame-retardant fiber is subjected to an external force sufficient to destroy the basic structure of the fiber, the cortex will basically not fall off.
[0050] It is worth noting that the flame retardant effect of the cortex is actually the result of the joint effect of the first flame retardant and the second flame retardant, because the surface layer of the fiber core is actually composed of the first flame retardant and cellulose, that is, the cortex includes the first flame retardant, cellulose and modified graphene oxide loaded with the second flame retardant.
[0051] In the present invention, the flame retardant effect is achieved by "fiber core + skin layer". In actual implementation, the flame retardant effect of the skin layer is the main one, and the fiber core is the auxiliary one. However, it is worth emphasizing that the addition of the first flame retardant in the fiber core is indispensable, otherwise the outer flame retardant layer may be intact and still functioning, but the core has been damaged due to high temperature.
[0052] Specifically, the first flame retardant is one or more of kaolin, montmorillonite, silica powder, and talc. The first flame retardant is an inorganic flame retardant, which is easy to disperse, has no metal ion impurities, is easy to mix with the NMMO solution, and has a high safety factor; flame retardants containing metal ions are easy to decompose and can cause explosions in severe cases.
[0053] Specifically, in the fiber core, the mass content of the first flame retardant is 8-11%, and / or the diameter of the fiber core is 7-12 μm. The core diameter mainly affects the fiber strength. If the content of the first flame retardant in the core is too low, it will lead to poor flame retardancy; if the content is too high, the fiber strength will be damaged. The diameter of the core determines the diameter of the final finished fiber. The core of the above diameter is suitable for the preparation of various downstream products while ensuring the strength. If the diameter of the finished fiber is too low or too high, it will be unfavorable for subsequent processing and product manufacturing.
[0054] Since the amount of flame retardant added to the core (i.e., the fiber body) of the present invention is very small, not exceeding 11wt.%, under the condition of the same flame retardant performance, the flame retardant fiber has a specific strength that is better than the flame retardant lyocell fiber in the prior art, and a breaking strength of not less than 4.5cN / dtex. The strength can meet the use requirements, basically reaching the level of conventional lyocell fibers and having good spinnability. Good spinnability is mainly reflected in the following two aspects:
[0055] Physical properties: Under the premise of ensuring the fiber breaking strength, finer fibers can be spun to meet most downstream usage scenarios, and the fiber strands are uniform and the curl is stable.
[0056] Appearance: The flame-retardant fiber provided by the present invention is free of lint and has uniform coloring.
[0057] Specifically, the second flame retardant is a mixture of component A and component B, and the mass ratio of component A to component B is 1:1-9;
[0058] The second flame retardant in the above ratio can form a good nitrogen-phosphorus synergistic effect. The interaction of the two elements during pyrolysis and combustion enhances the flame retardant effect of the material. Too much or too little addition of any component will destroy the synergistic effect, thereby causing a decrease in flame retardancy.
[0059] Wherein, component A is one of melamine, dicyandiamide, guanidine carbonate, guanidine phosphate, condensed guanidine phosphate, guanidine sulfamate and their derivatives; component B is tetrakis(hydroxymethyl)phosphonium sulfate or KWB. The above substances are easy to disperse and grind, and convenient to control the particle size. They are relatively mature commercial flame retardants and can be purchased directly. The above substances of common specifications can meet the implementation requirements of the present invention.
[0060] Specifically, in the modified graphene oxide loaded with the second flame retardant, the mass ratio of the second flame retardant to the graphene oxide is 10 to 20: 1. The amount of the second flame retardant added matches the specific surface area and loading capacity of the graphene oxide. Too much flame retardant cannot be stably loaded on the graphene oxide, and too little flame retardant will lead to a decrease in flame retardancy.
[0061] Exemplarily, the preparation process of modified graphene oxide is as follows: add graphene oxide to a dispersion kettle, stir for 30min to 1h, then add the second flame retardant in proportion, stir for 10min to 15min, transfer to a basket or horizontal grinder for grinding and dispersion, the speed is 1500 to 2500rpm, the grinding time is 10 to 20min, and the laser particle size analyzer is tested to have D90≤2μm, thus obtaining modified graphene oxide. The dispersion of modified graphene oxide can be prepared by ultrasonic-assisted wet grinding and dispersion process.
[0062] Specifically, in the cortex, the mass content of modified graphene oxide is 0.5-2% of the mass of the fiber in the cortex; and / or, the thickness of the cortex is 0.5-2 μm. Specifically, the mass content of modified graphene oxide in the cortex is 0.5-2% of the mass of the fiber in the cortex. Too low a content will damage the flame retardant properties, and too high a content will reduce the strength of the finished fiber; the thickness of the cortex is 0.5-2 μm, and the above thickness is roughly the depth that the modified graphene oxide can enter the cortex. During the coagulation bath process, the fiber will be stretched to a certain extent. At a certain spinning speed, the fiber molecular orientation is stable, and the depth of the modified graphene oxide entering the epidermis is basically fixed. Too thin a cortex will damage the flame retardant effect, and too thick a cortex will affect the comprehensive performance of the fiber (mainly strength).
[0063] The present invention also provides a method for preparing the flame-retardant lyocell fiber, comprising the following specific steps:
[0064] S1: taking a dispersant, a first flame retardant, and deionized water to prepare a first flame retardant dispersion;
[0065] S2: mixing the first flame retardant dispersion with the cellulose pulp and the first NMMO aqueous solution, heating, dissolving and dehydrating to obtain a spinning solution;
[0066] S3: preparing a modified graphene oxide dispersion loaded with a second flame retardant, and mixing the modified graphene oxide dispersion with a second NMMO aqueous solution to prepare a coagulation bath solution;
[0067] S4: After spinning, the spinning solution enters a coagulation bath and is post-treated to obtain the flame-retardant lyocell fiber.
[0068] Specifically, the composition of the first flame retardant dispersion in step S1 is 0.5-2 parts of dispersant, 5-15 parts of flame retardant, and 80-100 parts of water by mass; wherein the dispersant is a modified lignin sulfonate dispersant. Currently, based on the comprehensive consideration of cost and dispersion effect, modified sodium lignin sulfonate is generally selected, and the general commercially available model / specification can meet the implementation needs. The addition of the dispersant is to ensure that the flame retardant can be evenly dispersed; too much dispersant will affect the rheological properties of the dispersion, and then affect the mixing effect with the spinning solution; too little will affect the dispersion effect.
[0069] Specifically, in step S2, the mass ratio of the first flame retardant dispersion, cellulose pulp, and the first NMMO aqueous solution is 10-20:55-65:20-25; if the flame retardant content is too high, the dispersion stability is poor, which affects the mixing effect and ultimately affects the fiber strength; if it is too low, it will affect the flame retardant effect; cellulose pulp is the main matrix of the fiber, and the amount added should be more under the premise of ensuring the flame retardant effect and dispersion performance. It has been verified that the addition amount (mass ratio) is 55-65; the first NMMO aqueous solution is added to ensure the viscosity of the spinning solution, and the final concentration of NMMO in the spinning solution will be adjusted by dehydration and other processes later;
[0070] The mass concentration of NMMO in the first NMMO aqueous solution is 50%, and the mass concentration of NMMO in the spinning solution is 72-88%. The above NMMO concentration can ensure the spinning viscosity required for dry-jet wet spinning. Dry-jet wet spinning requires a high-viscosity spinning solution. The concentration and viscosity of NMMO are closely related. Too high or too low NMMO concentration will cause the viscosity of the spinning solution to not meet the requirements. The NMMO in the first NMMO aqueous solution should not be too low, so as to avoid the subsequent dehydration process taking too long.
[0071] Specifically, the volume ratio of the modified graphene oxide dispersion to the second NMMO aqueous solution in step S3 is 1:1; wherein the mass concentration of the modified graphene oxide dispersion is 5% to 15%, and the solvent is water; the mass concentration of NMMO in the second NMMO aqueous solution is 10% to 20%. Too much addition of the modified graphene oxide dispersion will lead to poor coagulation effect, resulting in rough cortex and affecting quality; too little addition will lead to insufficient loading of modified graphene oxide in the cortex, affecting the flame retardant effect.
[0072] Specifically, the coagulation bath temperature is 15-30°C, for example, 15, 18, 20, 23, 25, 28, 30°C. If the coagulation bath temperature is too high, the fiber will not be fully coagulated; if the coagulation bath temperature is too low, the fiber will coagulate too quickly, and the modified graphene oxide will penetrate shallowly into the fiber surface, which is not conducive to the comprehensive performance and flame retardant properties of the fiber.
[0073] Specifically, the structure and size of the skin layer are also related to the spinning speed. Experimental verification shows that when the spinning speed is 40 to 60 m / min, the flame retardant fiber has good comprehensive performance.
[0074] Preferably, the coagulation bath may be provided with an automatic circulating liquid supply component to ensure the stability of the concentration of modified graphene oxide around the fibers in the coagulation bath.
[0075] Specifically, the post-processing steps in step S4 include washing, chopping, steaming and drying.
[0076] Example 1
[0077] S1: taking modified sodium lignin sulfonate, kaolin, and deionized water in a ratio of 0.5:10:80 to prepare a first flame retardant dispersion;
[0078] S2: mixing the first flame retardant dispersion with cellulose pulp and the first NMMO aqueous solution, heating, dissolving and dehydrating to obtain a spinning solution, wherein the mass ratio of the first flame retardant dispersion, the cellulose pulp and the first NMMO aqueous solution is 15:58:22;
[0079] S3: preparing a modified graphene oxide dispersion loaded with a second flame retardant by an ultrasonic-assisted wet grinding dispersion process, wherein the mass ratio of the second flame retardant to graphene oxide in the modified graphene oxide is 10:1, and mixing the modified graphene oxide dispersion with a second NMMO aqueous solution to prepare a coagulation bath solution;
[0080] Wherein: the second flame retardant is a mixture of melamine and tetrakis(hydroxymethyl)phosphonium sulfate, and the mass ratio of the components melamine to tetrakis(hydroxymethyl)phosphonium sulfate is 1:2;
[0081] The volume ratio of the modified graphene oxide dispersion to the second NMMO aqueous solution is 1:1; wherein the mass concentration of the modified graphene oxide dispersion is 10%, and the solvent is water; the mass concentration of NMMO in the second NMMO aqueous solution is 13%;
[0082] S4: After the spinning solution is filtered and degassed, it enters the coagulation bath after being discharged through the metering pump and the spinneret. The coagulation bath temperature is 25°C and the spinning speed is 50m / min. After washing, cutting, steaming, drying and packaging, the flame-retardant lyocell fiber is obtained.
[0083] According to the test, the LOI index of the lyocell fiber is 28.5%, the breaking strength is 4.5 cN / dtex, and the LOI index can be maintained above 28% after 30 times of washing.
[0084] Example 2
[0085] S1: taking modified sodium lignin sulfonate, montmorillonite and deionized water in a ratio of 2:8:95 to prepare a first flame retardant dispersion;
[0086] S2: mixing the first flame retardant dispersion with cellulose pulp and the first NMMO aqueous solution, heating, dissolving and dehydrating to obtain a spinning solution, wherein the mass ratio of the first flame retardant dispersion, the cellulose pulp and the first NMMO aqueous solution is 10:65:21;
[0087] S3: preparing a modified graphene oxide dispersion loaded with a second flame retardant by an ultrasonic-assisted wet grinding dispersion process, wherein the mass ratio of the second flame retardant to graphene oxide in the modified graphene oxide is 13:1, and mixing the modified graphene oxide dispersion with a second NMMO aqueous solution to prepare a coagulation bath solution;
[0088] Wherein: the second flame retardant is dicyandiamide and KWB is a mixture of dicyandiamide and The mass ratio of KWB is 1:7;
[0089] The volume ratio of the modified graphene oxide dispersion to the second NMMO aqueous solution is 1:1; wherein the mass concentration of the modified graphene oxide dispersion is 5%, and the solvent is water; the mass concentration of NMMO in the second NMMO aqueous solution is 17%;
[0090] S4: After the spinning solution is filtered and degassed, it is fed into a coagulation bath through a metering pump and a spinneret. The coagulation bath temperature is 25°C and the spinning speed is 60 m / min. After washing, cutting, steaming, drying and packaging, the flame-retardant lyocell fiber is obtained.
[0091] According to the test, the LOI index of the lyocell fiber is 28.3%, the breaking strength is 4.7 cN / dtex, and after 30 times of washing, the LOI index can be maintained above 28.1%.
[0092] Example 3
[0093] S1: taking modified sodium lignin sulfonate, silicon dioxide powder and deionized water in a ratio of 1:5:85 to prepare a first flame retardant dispersion;
[0094] S2: mixing the first flame retardant dispersion with cellulose pulp and the first NMMO aqueous solution, heating, dissolving and dehydrating to obtain a spinning solution, wherein the mass ratio of the first flame retardant dispersion, the cellulose pulp and the first NMMO aqueous solution is 13:55:23;
[0095] S3: preparing a modified graphene oxide dispersion loaded with a second flame retardant by an ultrasonic-assisted wet grinding dispersion process, wherein the mass ratio of the second flame retardant to graphene oxide in the modified graphene oxide is 15:1, and mixing the modified graphene oxide dispersion with a second NMMO aqueous solution to prepare a coagulation bath solution;
[0096] Wherein: the second flame retardant is a mixture of guanidine carbonate and tetrakis hydroxymethyl phosphonium sulfate, and the mass ratio of the components guanidine carbonate and tetrakis hydroxymethyl phosphonium sulfate is 1:5;
[0097] The volume ratio of the modified graphene oxide dispersion to the second NMMO aqueous solution is 1:1; wherein the mass concentration of the modified graphene oxide dispersion is 8%, and the solvent is water; the mass concentration of NMMO in the second NMMO aqueous solution is 15%;
[0098] S4: After filtering and degassing, the spinning solution is fed into a coagulation bath through a metering pump and a spinneret. The coagulation bath temperature is 25°C and the spinning speed is 55 m / min. After washing, cutting, steaming, drying and packaging, the flame-retardant lyocell fiber is obtained.
[0099] According to the test, the LOI index of the lyocell fiber is 28.7%, the breaking strength is 4.8 cN / dtex, and after 30 times of washing, the LOI index can be maintained above 28.4%.
[0100] Example 4
[0101] S1: Measure modified sodium lignin sulfonate, "kaolin + silica powder" mixed powder (mass ratio 1:1), and deionized water in a ratio of 1.5:13:100 to prepare a first flame retardant dispersion;
[0102] S2: mixing the first flame retardant dispersion with cellulose pulp and the first NMMO aqueous solution, heating, dissolving and dehydrating to obtain a spinning solution, wherein the mass ratio of the first flame retardant dispersion, the cellulose pulp and the first NMMO aqueous solution is 20:60:25;
[0103] S3: preparing a modified graphene oxide dispersion loaded with a second flame retardant by an ultrasonic-assisted wet grinding dispersion process, wherein the mass ratio of the second flame retardant to graphene oxide in the modified graphene oxide is 19:1, and mixing the modified graphene oxide dispersion with a second NMMO aqueous solution to prepare a coagulation bath solution;
[0104] Wherein: the second flame retardant is guanidine sulfamate and KWB is a mixture of guanidine sulfamate and The mass ratio of KWB is 1:3;
[0105] The volume ratio of the modified graphene oxide dispersion to the second NMMO aqueous solution is 1:1; wherein the mass concentration of the modified graphene oxide dispersion is 15%, and the solvent is water; the mass concentration of NMMO in the second NMMO aqueous solution is 18%;
[0106] S4: After filtering and degassing, the spinning solution is fed into a coagulation bath through a metering pump and a spinneret. The coagulation bath temperature is 25°C and the spinning speed is 45 m / min. After washing, cutting, steaming, drying and packaging, the flame-retardant lyocell fiber is obtained.
[0107] According to the test, the LOI index of the lyocell fiber is 29.1%, the breaking strength is 4.6 cN / dtex, and after 30 times of washing, the LOI index can be maintained above 28.6%.
[0108] Example 5
[0109] S1: taking modified sodium lignin sulfonate, talcum powder and deionized water in a ratio of 1:15:90 to prepare a first flame retardant dispersion;
[0110] S2: mixing the first flame retardant dispersion with cellulose pulp and the first NMMO aqueous solution, heating, dissolving and dehydrating to obtain a spinning solution, wherein the mass ratio of the first flame retardant dispersion, the cellulose pulp and the first NMMO aqueous solution is 17:57:24;
[0111] S3: preparing a modified graphene oxide dispersion loaded with a second flame retardant by an ultrasonic-assisted wet grinding dispersion process, wherein the mass ratio of the second flame retardant to graphene oxide in the modified graphene oxide is 17:1, and mixing the modified graphene oxide dispersion with a second NMMO aqueous solution to prepare a coagulation bath solution;
[0112] Wherein: the second flame retardant is condensed guanidine phosphate and KWB is a mixture of guanidine phosphate and The mass ratio of KWB is 1:9;
[0113] The volume ratio of the modified graphene oxide dispersion to the second NMMO aqueous solution is 1:1; wherein the mass concentration of the modified graphene oxide dispersion is 13%, and the solvent is water; the mass concentration of NMMO in the second NMMO aqueous solution is 10%;
[0114] S4: After filtering and degassing, the spinning solution is fed into a coagulation bath through a metering pump and a spinneret. The coagulation bath temperature is 25°C and the spinning speed is 40 m / min. After washing, cutting, steaming, drying and packaging, the flame-retardant lyocell fiber is obtained.
[0115] According to the test, the LOI index of the lyocell fiber is 28.9%, the breaking strength is 4.5 cN / dtex, and the LOI index can be maintained above 28.5% after 30 times of washing.
[0116] The diameter of the lyocell fibers prepared in Examples 1 to 5 is 13 μm (there is an inevitable error), the initial LOI index is not less than 28.3%, the breaking strength is ≥4.5 cN / dtex, and after 30 washes, the LOI index can be maintained above 28.1%, and the flame retardant effect and fiber strength are excellent. In comparison, the fiber with a higher amount of flame retardant added and a lower spinning speed (slightly thicker skin) has better flame retardant properties, but the breaking strength has a slight decrease, the overall performance is excellent, and it has a significant improvement over the prior art.
[0117] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A flame retardant lyocell fiber, characterized in that: The invention comprises a fiber core and a skin layer directly formed on the surface of the fiber core, wherein the fiber core comprises a first flame retardant and cellulose, and the skin layer comprises modified graphene oxide loaded with a second flame retardant.
2. The flame retardant lyocell fiber according to claim 1, characterized in that: The fiber core is formed by spinning a spinning solution including a first flame retardant and cellulose.
3. The flame retardant lyocell fiber according to claim 2, characterized in that: The skin layer is formed directly on the surface of the fiber core when the fiber core enters a coagulation bath containing modified graphene oxide loaded with a second flame retardant.
4. The flame retardant lyocell fiber according to claim 1, characterized in that: The skin layer is directly formed on the surface layer of the fiber core through double diffusion effect and micro-swelling effect.
5. The flame retardant lyocell fiber according to any one of claims 1 to 4, characterized in that: The first flame retardant is one or more of kaolin, montmorillonite, silica powder and talc powder.
6. The flame retardant lyocell fiber according to any one of claims 1 to 4, characterized in that: In the fiber core, the mass content of the first flame retardant is 8-11%, and / or the diameter of the fiber core is 7-12 μm.
7. The flame retardant lyocell fiber according to any one of claims 1 to 4, characterized in that: The second flame retardant is a mixture of component A and component B, and the mass ratio of component A to component B is 1:1-9; Wherein, component A is one of melamine, dicyandiamide, guanidine carbonate, guanidine phosphate, condensed guanidine phosphate, guanidine sulfamate and their derivatives; component B is tetrakis(hydroxymethyl)phosphonium sulfate or KWB.
8. The flame retardant lyocell fiber according to any one of claims 1 to 4, characterized in that: In the modified graphene oxide loaded with the second flame retardant, the mass ratio of the second flame retardant to the graphene oxide is 10 to 20:
1.
9. The flame retardant lyocell fiber according to any one of claims 1 to 4, characterized in that: In the skin layer, the mass content of modified graphene oxide is 0.5-2%; and / or the thickness of the skin layer is 0.5-2 μm.
10. A method for preparing the flame-retardant lyocell fiber according to any one of claims 1 to 9, characterized in that: The specific steps include: S1: taking a dispersant, a first flame retardant, and deionized water to prepare a first flame retardant dispersion; S2: mixing the first flame retardant dispersion with the cellulose pulp and the first NMMO aqueous solution, heating, dissolving and dehydrating to obtain a spinning solution; S3: preparing a modified graphene oxide dispersion loaded with a second flame retardant, and mixing the modified graphene oxide dispersion with a second NMMO aqueous solution to prepare a coagulation bath solution; S4: After spinning, the spinning solution enters a coagulation bath and is post-treated to obtain the flame-retardant lyocell fiber.
Citation Information
Patent Citations
Nylon 6 fiber and preparation method thereof
CN108048929A
Compound flame retardant modified Lyocell fiber and preparation method thereof
CN117904736A
Reticulated absorbent composite
CN1427705A